Using the Clinical competency assessment to assess how medical students apply behavioural sciences: Presenter(s): Jacqueline Lavallee, University of Manchester, United Kingdom. (April 2023) - Shepherd, Sarah; Hart, Jo; Byrne-Davis, Lucie
Abstract : Background: Conversations about behaviour change are becoming increasingly more important within healthcare settings. We designed and implemented health-psychology-informed clinical communication sessions and a Clinical competency assessment (CCA) station for year 1 medical students. Methods: We evaluated structural alignment throughout the years 1-5 psychology curriculum and explored areas for integration into skills practice. This led to additional teaching and learning content, a behaviour change CCA station in years 1, 3 and 4 and amendments to CCA global marking schemes. The year 1 behaviour change station included a 4-minute consultation exploring smoking behaviours with a standardised patient [SP] and three case study questions about behaviour change theory. We recruited 14 examiners with appropriate professional expertise and delivered this CCA station to 459 year 1 medical students in 2021 and 2022. Findings: In 2021, 87% students passed the behaviour change station compared with 98% who passed the history taking only station. Students asked the SP theory-informed questions to gather information about their smoking; but some found it challenging to combine these questions with their usual communication skills and to demonstrate knowledge of the underlying theory during the examiner questions. Of the 60 students who failed the station, 82% failed the examiner questions, 1% failed the consultation and 17% failed both aspects. 2022 CCA assessment data will be available in June. Discussion: Further development of the teaching and learning activities throughout medical school is needed to support students to use behaviour change theory to guide their consultations. The training of skills tutors and SPs in these theories and behaviour change conversation skills is integral to augment this learning.